The Sensory Machinery of the Head Louse Pediculus humanus capitis: From the Antennae to the Brain - Ortega Insaurralde, Isabel; Minoli, Sebastián; Toloza, Ariel Ceferino; Picollo, María Inés; Barrozo, Romina B. (Frontiers in Physiology, 2019)
Insect antennae are sophisticated sensory organs, usually covered with sensory structures responsible for the detection of relevant signals of different modalities coming from the environment. Despite the relevance of the head louse Pediculus humanus capitis as a human parasite, the role of its antennal sensory system in the highly dependent relation established with their hosts has been barely studied. In this work, we present a functional description of the antennae of these hematophagous insects by applying different approaches, including scanning electron microscopy (SEM), anterograde antennal fluorescent backfills, and behavioral experiments with intact or differentially antennectomized lice. Results constitute a first approach to identify and describe the head louse antennal sensilla and to determine the role of the antenna in host recognition. SEM images allowed us to identify a total of 35–40 sensilla belonging to seven different morphological types that according to their external architecture are candidates to bear mechano-, thermo-, hygro-, or chemo-receptor functions. The anterograde backfills revealed a direct neural pathway to the ipsilateral antennal lobe, which includes 8–10 glomerular-like diffuse structures. In the two-choice behavioral experiments, intact lice chose scalp chemicals and warm surfaces (i.e., 32°C) and avoided wet substrates. Behavioral preferences disappeared after ablation of the different flagellomeres of their antenna, allowing us to discuss about the location and function of the different identified sensilla. This is the first study that integrates morphological and behavioral aspects of the sensory machinery of head lice involved in host perception.